The Effect of Promoters on the Activity of Prepared Zeolite Catalyst in FCC Process - A-K Mohammed, Abdul Halim; Ali Dahyool, Nuha (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Faujasite type NaY zeolite catalyst was prepared from locally available kaolin, then the prepared NaY zeolite have been modified by exchanging of sodium ion with ammonium to produce NH4Y zeolite. NH4Y zeolite was converted to HY zeolite by ion exchanging with oxalic acid. Zinc and nickel promoters have been added to the prepared HY zeolite catalyst, and the effect of these promoters on the catalytic activity of the prepared HY catalyst was studied in fluid catalytic cracking process using light gas oil as a feedstock. The experimental results show that the promoted catalyst gives higher gas oil conversion and gasoline yield than HY zeolite catalyst at the same reaction temperature and WHSV. It was also found that the promoted catalyst gives gasoline with lesser olefin content and higher aromatics compared with the gasoline produced by HY catalyst.